The extraction of amino acids from papaya leaves using supercritical carbon dioxide with water - Nur Hazila, Mohamad Azmi (2010)
In this study, a new extraction method for the isolation papain form papaya leaves (carica papaya sp.) is being developed using supercritical carbon dioxide (SC-CO2) with water. The parameters of temperature, extraction time and comparison yield with hot water extraction were studied. Results indicated that temperature and extraction time had significant effect on the extraction yield. The highest extraction yield (0.56mol/liter) amino acid was obtained at 300 bar, 50 °C and 2hours. Extracted yields were then analysed by UV-vis spectrophotometer at 660nm and casein as a substrate. The composition of the extracted yields was greatly impacted by the operating conditions. At the best extraction condition (300 bar, 50 °C and 2 hours), amino acid had the highest concentration (0.56mol/liter) among all the other detected samples. The present findings showed that papaya leaves is a potential source of papain enzymes compounds. In addition, supercritical carbon dioxide extraction is a promising a high yield and alternative process for construct the papain compounds from papaya (carica papaya sp.) leaves which is by-product raw material. For further study, High Performance Liquid Chromatography (HPLC) should be using to analyses the enzyme to more accurate result.